Comparison of Muscle Energy Techniques and Myofascial Release in Premenopausal Women with Fibromyalgia - Samar Negm; Abeer ElDeeb; Mai Shehata; ElSayed Abdou; Efrem Kentiba; Elham Hassan (Здоров’я, спорт, реабілітація)
Background and Purpose